Experimental Study on the Permeation and Migration Rules of Pressurized Water in Textile-Reinforced Concrete (TRC) - Boxin Wang (MDPI AG, 2021)
As a new type of repairing and reinforcing material, textile-reinforced concrete (TRC) is often used to improve mechanical properties and durability of offshore, port, and hydraulic structures in the corrosive environment. In order to investigate how to quantify the permeability performance of TRC under external pressurized water, standard concrete permeability tests, nuclear magnetic resonance (NMR) tests, and scanning electron microscope (SEM) tests were conducted. These tests considered the effects of fiber grid size, Tex content, and water–cement ratio on the impermeability of TRC. Experimental results show that water gathers around the fiber bundles and migrates upwards along the longitudinal fiber under external water pressure and seeps out from the upper surface of the concrete specimen. Furthermore, based on the concentric annular slit flow theory and hydropower similarity principle, this study established a formula for the permeability of TRC and the calculated values are in good agreement with the experimental values.